Cryptococcemia in a patient with COVID‐19: A case report - Khatib, Mohamad Y. (Clin Case Rep, 2020)
The authors urge clinicians to balance the use of Immunosuppressant drugs and tocilizumab for COVID‐19 patients to avoid the development of infections like Cryptococcemia, leading to death within 30 days.